The Power of the Durbin-Watson and Geary Tests: Comment and Further Evidence - Harrison, M. J. (The Review of Economics and Statistics, 1975)
Alterman, J., Interindustry Employment Requirements, Monthly Labour Review (July 1965), 841850. Carter, A. P., Structural Change in the American Economy, Harvard Studies in Technology and Society (Cambridge, Harvard University Press, 1970), 34. Economic Commission for Europe (ECE) Standardised Tables of ECE countries for Years Around 1959, (1970), 1-31. (mimeo). Lancaster, K., Mathematical Economics (New York: Macmillan Company, 1968), 86. Leontief, W. W., The Structure of American Economy 1919-39 (Oxford University Press, 1960), 160. U.K., Central Statistical Office, Input-Output Tables for the United Kingdom, Studies in Official Statistics, no. 16 (H.M.S.O. 1970), 1-89. U.S. Bureau of Commerce, Office of Business Economics, Input-Output Structure of the U.S. Economy: 1963, Survey of Current Business (Nov. 1969), 16-47.